PENGARUH PERILAKU MASYARAKAT TERHADAP PENGELOLAAN SAMPAH DI DESA KEBUNDADAP TIMUR KECAMATAN SARONGGI KABUPATEN SUMENEP - Dela Aprilia Andina; Anita Intan Nura Diana; Subaidillah Fansuri (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
Critical population expansion and changes in individual utilization design indirectly increase the volume, type, and characteristics of waste, much more differently. Home life also generates waste. Information from the BPS in 2022, the population in the village of Kebundadap Timur is 3060 people. Many people there are still not ready to manage their waste properly. Residents like to throw their garbage into the river or by burning it around the house. Thus, the problem of family waste is also experienced by the people of East Kebundadap village. The purpose of this study was to determine the effect of community behavior on waste management in East Kebundadap village. This study uses a quantitative approach with associative research methods. The population in this study was the people of Kebundadap Timur Village, amounting to 3060 people with a sampling technique using purposive sampling with an error rate of 10% which resulted in 97 members as respondents in this study. The instrument used by distributing questionnaires to respondents. Analysis of the data used is simple linear regression analysis. Based on the results of the research and discussion that has been described by the author about the influence of community behavior on waste management in the village of Kebundadap Timur, it can be said that the influence of community behavior on waste management in the Village of Kebundadap Timur is a positive influence and means that community behavior is able to improve management This is evidenced by the results of analysis using multiple linear regression, namely the regression equation of Y = 8.084 + 0.756X, based on the R value of 0.663 which means it has a strong relationship between variables and variables, based on the results of the F test and T test which also concludes that community behavior variables have a significant effect on waste management in East Kebundadap Village.